Peranan Rasa Syukur terhadap Kepuasan Hidup Remaja Madya SMA saat Pembelajaran Jarak Jauh (PJJ) - Alda Clarissa Sunaryo; Erik Wijaya (Provitae: Jurnal Psikologi Pendidikan, 2021)
In the current situation of the COVID-19 pandemic in Indonesia, it has an impact on the field of education which results in changes in the learning system which carried out using a distance learning system. The distance learning system performed by students and teachers has negative impacts and positive impacts. One of the positive impacts is students can learn to feel grateful for the conditions they experienced during the COVID-19 pandemic. When students have gratitude, students can enjoy experiences and difficult situations during the COVID-19 pandemic which makes them have to do distance learning as a positive thing and it will lead to life satisfaction in students. Therefore, this study aims to determine the role of gratitude on life satisfaction in middle adolescents in senior high school during distance learning. This study was conducted on 1298 senior high school students aged 15-18 years old who are doing distance learning in Indonesia. The research method used is a non-experimental quantitative research method. The gratitude measure instrument used is The Gratitude Questionnaire-Six Item Form (GQ-6) and the student’s life satisfaction measure instrument used is the Multidimensional Student’s Life Satisfaction Scale (MSLSS). Based on the Structural Equation Model (SEM) analysis through the structural model of gratitude on student’s life satisfaction, the results obtained in this study with t-value = 14.56 > 1.96 or R2 value is 51%. Thus, gratitude has a positive and significant role of 51% on life satisfaction in middle adolescents in senior high school during distance learning.